ANIMASI INTERAKTIF PADA MATA PELAJARAN AGAMA ISLAM - Dewi Immaniar Desrianti; Sudaryono Sudaryono; Rahmah Diana (Universitas Raharja, 2019)
Learning in the form of animation is one form of utilization of TIK Multimedia that needs to be developed in the world of education. Especially Islamic religious lessons where learners are always saturated and feel bored when the teacher is giving a subject matter. As an alternative problem solving is to provide a new innovation that is Interactive Animation. Interactive Animation is an integrated learning system that will be applied and is one form of improvement in towards a modern and quality education. The reason for the implementation of Interactive Animation method is hope to provide an effective, innovative, creative, and fun learning system. In this learning application Presenting the material interactively accompanied by Text, Image, Animation, video, and religious song. The process of making the application is done starting from the stage of determining the target, the selection of material topics, design, data collection, manufacture and testing. Objectives applied Interactive animation is to eliminate the atmosphere of saturation and passive in the learning process and the interactive approach of both students and teachers With this practical learning hope to help improve the quality of teaching-learning process in the form of Interactive Animation in every school. So this method of application can be made in order to improve quality, and quality in education. And as a reference material in order to be made an evaluation material that can be developed for the better.